1997
DOI: 10.1007/s004840050042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute hyperthermia on the carotid baroreflex control of heart rate in humans

Abstract: The purpose of this study was to examine the effect of hyperthermia on the carotid baroreceptor-cardiac reflexes in humans. Nine healthy males underwent acute hyperthermia (esophageal temperature -38.0 degrees C) produced by hot water-perfused suits. Beat-to-beat heart rate (HR) responses were determined during positive and negative R-were-triggered neck pressure steps from +40 to -65 mm Hg during normothermia and hyperthermia. The carotid baroreceptor-cardiac reflex sensitivity was evaluated from the maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
30
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 27 publications
6
30
0
Order By: Relevance
“…A lack of change in baroreflex gain is consistent with prior findings (2,26,27), but it is in contrast to one study (5). Conflicting findings between these studies are likely due to the methodology of assessing baroreflex regulation.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…A lack of change in baroreflex gain is consistent with prior findings (2,26,27), but it is in contrast to one study (5). Conflicting findings between these studies are likely due to the methodology of assessing baroreflex regulation.…”
Section: Discussionsupporting
confidence: 84%
“…In humans, we (2) and others (26) reported that the gain of the carotid-cardiac baroreflex was not significantly affected by whole body heating, whereas the gain of the carotid-vasomotor baroreflex was significantly attenuated in this environment (2). Furthermore, we reported that the transfer function gain of the relationship between spontaneous fluctuations in blood pressure and heart rate was significantly attenuated within the high-frequency range (5).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, we and others have shown that whole body heating does not alter the maximal gain of baroreflex control of heart rate during carotid baroreceptor perturbations (4,35) or during acute changes in arterial blood pressure (7,36). Moreover, the gain expressing the relationship between blood pressure and muscle sympathetic nerve activity (MSNA) was unaffected by whole body heating (7).…”
mentioning
confidence: 93%
“…Compared with normothermic control, whole-body heating rapidly increases calf volume during the early phase of HUT, whereas whole-body cooling decreases the magnitude and the speed of change in calf volume 48) . Local heating to the legs in normothermia increases the blood flow in the warmed skin area and increases the speed of the change in calf volume the same nique, the effect of heat stress on the relationship between carotid distending pressure and HR has been examined in the supine position [50][51][52] . Prior reports showed that wholebody heating did not alter the sensitivity of the carotid baroreflex for controlling HR, as defined by the maximal slope of the linear portion of the baroreflex curve around the operating point, irrespective of heating levels [50][51][52] (Fig.…”
Section: Increase In Leg Venous Compliancementioning
confidence: 99%